Impact of crop-crop diversity on pod-borer (Helicoverpa armigera) of pigeonpea (Cajanus cajan) - Rao, M Srinvasa; Rao, C.A Rama; Vani, G Sree; Anjaiah, E (The Indian Journal of Agricultural Sciences, 2007)
An experiment was conducted during rainy (kharif) season 2003 and 2004 at Hyderabad to study the impact of crop -crop diversity on incidence of pod-borer [Helicoverpa armigera (Hubner)] on pigeonpea [Cajanus cajan (L.) Millsp]. The incidence of major pod-borer H. armigera varied temporally across cropping systems and significant fluctuation was noticed even at peak level of population (13-16 weeks after sowing). Intercropping also caused significant variation in pod and grain damage by pod-borers Maruca vitrata (Geyer), Exelastis atomosa (Walsingham) and Melanagromyza obtusa (Malloch). The intercrops, viz sorghum (Sorghum bicolor L.), groundnut (Arachis hypogaea L.) and blackgram (Vigna mungo (L.) Hepper) reduced the pod damage by H. armigera, M. vitrata, and M. obtusa significantly. The grain damage by lepidopteran borers was less in pigeonpea + sorghum (l5.15%), pigeonpea + groundnut (22.26%) and pigeonpea + blackgram (20.49%) intercropping systems. These effective cropping systems registered highest pigeonpea equivalent yields that was in the range of 0.97-1.1 1 tonnes/ha. Further these systems were more efficient agronomically in terms of land equivalent ratio (1.04-1.31), aggressivity (1.03-1.49), competitive ratio (1.77-1.97) and relative crowding coefficient (4.08 - 9.59). Economic analysis showed these intercropping systems to be more profitable than the sole pigeonpea.